AB0667 The effectiveness of therapeutic ultrasound in non-specific mechanical cervical pain and comparison of different application methods for clinical practice. (23rd January 2014) - Celik, O.; Ketenci, A.; Esmaeilzadeh, S.; Sindel, D.
Abstract : Objectives: The aim of this study was to investigate the effectiveness of therapeutic ultrasound (US) in non-specific mechanical neck pain, and to compare the effects of intermittent and continuous US applications on pain severity and functional disability. Methods: Seventy-one patients, aged between 18 and 65, with non-spesific mechanical neck pain suffering from less than three months were included the study. After the baseline measurements, patients were randomized to three physical treatment groups. US was applied at 1.5 Watt/cm 2 power, 100 Hz, 1 MHz frequency with 50% duty cycle intermittently in the first group and 1.5 Watt/cm 2 power, 100 Hz, 1 MHz frequency continuously in the second group while the third group received sham US application during 10 sessions. Three groups were also treated with transcutaneous electrical nerve stimulation. Patients were evaluated by visual analog scale and algometer for pain severity and sensitivity level of painful point on cervical region, also neck disability index was used for assessment of functional disability. Active cervical range of motion was measured by using goniometer. Control measurements were done after physical therapy and three months later after therapy. Results: Fifty-three patients completed the study. Seventeen (32.1%) of them were in intermittent US group, 19 (35.8%) of them were in continuous US group and 17 (32.1%) of them were in placebo US group. The groups were homogeneous regarding to age, gender, body mass index and baseline measurements. Pain severity was improved statistically significant in three groups after the treatment and three months later after therapy (p<0.001). Pain pressure threshold (PPT) was increased statistically significant in the first and second group after the treatment (p<0.05), while PPT was decreased in control group. Three months later after therapy PPT was increased statistically significant in all of three groups (p<0.05). There were no statistically significant differences between three groups regarding to pain severity and PPT improvements (p>0.05). There were no statistically significant changes in cervical range of motion after intermittent US application (p>0.05). Cervical range of motion was statistically significant increased at three planes after continuous US application but, there were no significant differences between continuous and placebo applications (p>0.05). Continuous US was observed more effective than intermittent application in cervical rotation range when the groups were compared after the physical therapy sessions. Statistically significant improvement was observed in functional disability for all of three groups after physical therapy sessions and three months later after therapy (p>0.05). Continuous application was observed more effective when the group were compared in terms of functional recovery. Conclusions: Therapeutic US applications are effective in reducing the severity of pain and sensitivity level of painful point on cervical region by increasing PPT, furthermore it affects the functional status positively by increasing cervical range of motion. Disclosure of Interest: None Declared